Leader prototypicality moderates the relation between access to flexible work options and employee feelings of respect and leader endorsement. Issue 22 (15th December 2016) - Koivisto, Satu; Rice, Ronald E.
Abstract : Organizations are increasingly offering flexible work arrangements (FWA), which are associated with a variety of individual and organizational outcomes. Supervisors may support, discourage or prohibit employees' access to and use of such programs. These actions and decisions can affect employees' feelings of being respected, and their endorsement of their supervisor – that is, matters that affect employees' motivation to work in pursuit of group and organizational goals. In the present paper, we take a fresh look at these relationships by proposing, in line with the social identity approach, that they are moderated by leader in-group prototypicality (i.e. the supervisor's representativeness of group identity). Results from two large sample surveys a year apart at one organization show that employees with supervisors who allow more FWA feel more respected as well as express stronger endorsement of their leaders. Importantly, both of those relationships are moderated by the degree of the supervisor's in-group prototypicality, but in opposite ways. The association of FWA allowance with respect increases slightly under conditions of higher prototypicality. However, the association of FWA allowance with endorsement of leaders increases more strongly under conditions of lower prototypicality. The discussion considers theoretical, practical and research implications of these findings.